Analysis of pH and Total Coliform Bacteria Contamination in Rainwater Based on the Materials and Maintenance of Rainwater Harvesting Systems - Ashifatul Azizah; Khoiron Khoiron; Ellyke Ellyke; Muhammad Addin Rizaldi (Poltekkes Kemenkes Surabaya, 2026)
The present study investigates variations in the quality of rainwater, with a focus on the materials and maintenance practices employed in rainwater harvesting (RWH) systems within Ploso Hamlet, Plosobuden Village, Lamongan Regency. The aim of the present study is to monitor pH levels and to identify the presence of total coliform contamination. The present study employed a descriptive quantitative approach, with 30 RWH units being purposively selected from a total of 106. The data were collected through three means: observation, in-depth interviews, and laboratory testing. The result of this study shows that rainwater was contaminated with coliform bacteria, with a mean value of 3.6 MPN/100 ml and a maximum value of >1600 MPN/100 ml, which exceeds the standard for drinking water (0 MPN/100 ml). Furthermore, 48.3% of samples exhibited a pH value that exceeded the acceptable range, with the highest recorded value being 10.7. Maintenance was substandard, with 66.7% of respondents admitting to cleaning their tanks only once a year. Furthermore, none had received education on proper maintenance. In conclusion, the analysis indicates that harvested rainwater in Ploso Hamlet does not conform to the criteria for direct consumption. The study identifies the presence of biological contamination and improper pH levels as the primary causes of the water's unsuitability for human consumption. It is recommended that the knowledge base be augmented through the implementation of a health education programme, complemented by enhanced filtration measures.